Thermal investigation and infrared evolved gas analysis of solid trivalent lanthanide and yttrium alpha-hydroxyisobutyrates in N-2 and CO2 atmospheres - Caires, F. J. [UNESP]; Gomes, D. J. C. [UNESP]; Gigante, A. C. [UNESP]; Ionashiro, Massao [UNESP] (Elsevier B.V., 2014)
Solid-state Ln(C4H7O3)(3)center dot nH(2)O compounds, where Ln stands for trivalent lanthanides or yttrium and C4H7O3- is alpha-hydroxyisobutyrate, have been synthesized. Simultaneous thermogravimetry and differential thermal analysis (TG-DTA), elemental analysis, complexometry and TG-DSC coupled to infrared spectroscopy (FTIR) were used to characterize and to study the thermal behavior of these compounds in CO2 and N-2 atmospheres. The dehydration of the compounds occurs in a single (La to Nd, Tb to Tm and Y), two (Sm and Gd) and three (Eu) steps in N-2 atmosphere and a single (La, Ce, Tb to Tm and Y), two (Pr, Nd and Gd) and three (Sm and Eu) steps in CO2 atmosphere. The final residues of the thermal decomposition in N-2 atmosphere for europium to dysprosium, ytterbium and yttrium compounds up to 1000 degrees C were the respective oxides Ln(2)O(3) (Ln = Eu, Gd, Tb, Dy, Yb,Y) while for lanthanum, cerium praseodymium, neodymium, samarium, holmium, erbium, thulium and lutetium compounds, the mass loss is still being observed up to 1000 degrees C. In CO2 atmosphere, the final residue up to 1000 degrees C for all the compounds was the respective oxides, CeO2, Tb4O7 and Ln(2)O(3) (Ln = La, Pr to Gd, Dy to Lu and Y). (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Trivalent lanthanides; alpha-Hydroxyisobutyrate; Thermal behavior; Coupled thermogravimetry-infrared; spectroscopy